GAMBARAN IBU YANG MENGGUNAKAN KONTRASEPSI METODE OPERASI WANITA (MOW) DI WILAYAH KERJA PUSKESMAS SUMBER SARI BANTUL - Susanti, Tri (Akbid Wirabuana, 2022)
Mow or sterilization is the act of blocking or blocking the passage of sperm or eggs through surgical means to prevent fertilization. According to data from the Lampung Provincial Health Office in 2019, MOW KB participants were 16,659 (4.10%) and data from the Metro City Health Office was 662 (3.3%). From the data above, the lowest MOW coverage is in the sub-districts of metro south, metro north and metro center, as much as (3%), while the MOW coverage at Puskesmas Sumber Sari Bantul is 52 (2.65%) of the total MOW family planning users. The purpose of this study was to determine the description of mothers who used MOW contraception in the work area of Sumber Sari Bantul Health Center in 2019 with a population of 52 mothers. The sample used in this study was a total sampling of 52 mothers. The measuring instrument used is primary data with a measuring instrument in the form of a questionnaire. Data analysis with univariate analysis with frequency distribution. The results showed that the frequency distribution based on maternal age was the majority with age > 35 years as many as 49 mothers (94.2 %), multiparity parity as many as 49 mothers (94.2 %), artificial birth types as many as 36 (69.2% %), and children aged 0-1 months were 43 (82.7%). The conclusion obtained from this study is that it is hoped that health workers at the Sumber Sari Bantul Health Center and the UPTKB office can improve the quality of services through counseling and counseling about MOW contraception to prospective acceptors and working with cadres to jointly promote MOW contraception to prospective family planning acceptors.Keywords: MOW Contraception, Age, Parity, Type of Delivery, Child's Age